Price elasticity of household water demand in the Czech Republic - Jana Hortová; Ladislav Krištoufek (Charles University in Prague, Institute of Economic Studies (IES), 2014)
In the Czech Republic, water prices have been steadily increasing while water consumption has been decreasing during the last decades. A great deal of literature is devoted to the price elasticity of water demand but to the best of our knowledge, no similar study has been devoted entirely to the Czech Republic. In the paper, we examine the short and long-run price elasticities of water demand in the Czech Republic between years 2000 and 2011. We find that the water demand is inelastic (lower than one) with respect to water price regardless of the time period and the income elasticity is on the edge of statistical significance. Our inferences are in line with previous findings.
Keywords: C54; Q25; Q53; 330; water consumption; price elasticity; income elasticity